Cyclopentolate use disorder: a case report of intranasal misuse - Görgülü, Yasemin; Çöl Ateş, Işıl; Köse Çınar, Rugül; Sönmez, Mehmet Bülent (Journal of Dependence, 2015)
Anti-cholinergic drugs carry dependency risk. Cyclopentolate is a topical anticholinergic drug commonly used in ophthalmology clinics which possesses mydriatic and cycloplegic properties. A 28 year old male patient previously diagnosed with bipolar disorder was admitted to the psychiatric clinic with symptoms of depression. We learned that he has been using cylo-pentolate containing eye drops intranasally for pleasure for about one year. Hereby, we have reported a cyclopentolate use disorder case with comorbid bipolar disorder, which used cyclopentolate intranasally, different to other cases in the literature.